2021
DOI: 10.18196/ftl.v6i1.10175
|View full text |Cite
|
Sign up to set email alerts
|

EFL Speaking Fluency through Authentic Oral Production

Abstract: This article describes the development of speaking fluency through authentic oral production in a six-week action research study of a public high school in Guayaquil, Ecuador. The methodology included a pre-test and a post-test that measured quantitative aspects of student’s spoken fluency (speed, pauses, repetitions, and corrections), a survey with closed-ended questions that collected learners’ perspectives towards their own speaking fluency, and an interview that addressed students’ opinions towards the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Video as an interactive media enables learners to achieve English fluency. This idea is supported by findings conducted by (Lopez et al, 2021;Putri & Rahmani, 2019), who claimed that video is the ideal platform for fostering fluency and speaking accuracy. Respondents utilized these video-based tasks to reflect on their speaking accuracy and fluency errors, including utterance speed, tone, stress, pauses, repetitions, and corrections.…”
Section: Fluency and Accuracymentioning
confidence: 57%
“…Video as an interactive media enables learners to achieve English fluency. This idea is supported by findings conducted by (Lopez et al, 2021;Putri & Rahmani, 2019), who claimed that video is the ideal platform for fostering fluency and speaking accuracy. Respondents utilized these video-based tasks to reflect on their speaking accuracy and fluency errors, including utterance speed, tone, stress, pauses, repetitions, and corrections.…”
Section: Fluency and Accuracymentioning
confidence: 57%
“…In their study, Kana'an and Ahlullahsiddiqui (2021) promoted Saudi English majors' speaking fluency through the incidental learning of vocabulary as the students read varied written texts. On their part, Lopez, Becerra and Avila (2021) found that encouraging Ecuadorian senior high school students to record and post their own created videos on YouTube fostered their speaking fluency; they, also, found that most of their study participants had positive attitudes towards such an instructional procedure. Specifically, creating and posting these YouTube videos increased their normal speech rate as well as reduced their pauses, repetitions and corrections.…”
Section: Techniques Employed To Enhance Speaking Fluency Among Efl Le...mentioning
confidence: 99%
“…These studies have elucidated the benefits of multimodal composing for language learners’ multilingual identity development (Anderson & Macleroy, 2017; Kim, 2018; Kumagai et al, 2015) and learning of course content (Goulah, 2017; Yi, 2014). For example, creating L2 English vlogs helped high school students in Ecuador to augment their metalinguistic awareness (Lopez et al, 2021), or “the ability to distance oneself from the content of speech to reflect upon and manipulate the structure of language” (Altman et al, 2018, p. 3). In the study abroad context, multimodal composing through video reflections has also been found to promote metalinguistic awareness by encouraging learners of French to engage in practices of language rehearsal, language repair, and reflection on linguistic goals (Amgott, 2020).…”
Section: Theoretical Framework: Multimodalitymentioning
confidence: 99%